2021
DOI: 10.3390/antibiotics10020205
|View full text |Cite
|
Sign up to set email alerts
|

Natural Agents against Bovine Mastitis Pathogens

Abstract: Bovine mastitis is the most widespread and economically important disease worldwide. The present study aimed to determine bioactive compounds in two essential oils (EOs) from wild (Thymus serpyllum) and common thyme (Thymus vulgaris) and to assess the antioxidant potential as well as antibacterial efficacy of the EOs against mastitis-associated bacteria. The study also included antibiotic susceptibility tests. The strains were previously isolated from lactating animals with clinical and subclinical mastitis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 70 publications
2
48
0
Order By: Relevance
“…Antibiotics included in the testing were augmentin, amoxicillin, erythromycin, tetracycline, cloxacillin, gentamicin, cotrimoxazole, and chloramphenicol. According to Kovačević et al [ 54 ], the most used antibiotics in inflammation therapy in food animals are penicillin, streptomycin, gentamicin, tetracycline, cephalexin, sulfonamides, and enrofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics included in the testing were augmentin, amoxicillin, erythromycin, tetracycline, cloxacillin, gentamicin, cotrimoxazole, and chloramphenicol. According to Kovačević et al [ 54 ], the most used antibiotics in inflammation therapy in food animals are penicillin, streptomycin, gentamicin, tetracycline, cephalexin, sulfonamides, and enrofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…T. serpyllum is a suitable alternative to artificial fungicides because of the high content of monoterpene compounds. Kovacevic et al [ 15 ] determined the main compounds of T. serpyllum EO to be thymol, 54.17%; γ-terpinene, 22.18%; and p-cymene 16.66%. Thymol (15.21% and 41.8%) was the main compound of T. serpyllum EO in the studies of Šojić et al [ 16 ] and Tazabayeva and Sylibaeva [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These oils are used in medicine, cosmetics, food and as dietary supplements. Many studies have shown good antimicrobial effects of EOs against the common mastitis pathogens in vitro [ 9 , 10 ]. Additionally, in vivo experiments have demonstrated EOs’ effectiveness in mastitis treatment by improving udder condition, reducing number of somatic cells and elimination of intramammary infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%